2021
DOI: 10.1111/1462-2920.15358
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of bacterioplankton and its relationship with environmental factors in the upper reaches of the Heihe River in Qinghai Plateau

Abstract: Summary Planktonic microorganisms play a key role in the biogeochemical processes of the aquatic system, and they may be affected by many factors. High‐throughput sequencing technology was used in this study to investigate and study the bacterioplankton community of water bodies in the upper reaches of the Heihe River Basin in Qinghai Plateau. Results showed that Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria are the predominant phyla in this river section, while the main genera are Thiomonas, Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The above results indicate that N and P nutrients are the main factors driving the communities and function of bacterioplankton in the DJR. Similar to other lakes and reservoirs, T, pH, COD, COD Mn , Cond, and Chla are also important factors affecting the composition of the bacterioplankton communities in the DJR ( Liu et al, 2015 ; Chen Z. J. et al, 2020 ; Dong et al, 2020 ; Qian-Qian et al, 2021 ; Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The above results indicate that N and P nutrients are the main factors driving the communities and function of bacterioplankton in the DJR. Similar to other lakes and reservoirs, T, pH, COD, COD Mn , Cond, and Chla are also important factors affecting the composition of the bacterioplankton communities in the DJR ( Liu et al, 2015 ; Chen Z. J. et al, 2020 ; Dong et al, 2020 ; Qian-Qian et al, 2021 ; Sun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…Many studies have shown that bacterioplankton exhibit temporal and spatial variation characteristics under the influence of physicochemical properties such as T, pH, nutrients, and DO in the water body and hydrological factors such as flow velocity, flow rate, and water level ( Pearce, 2005 ; Qian-Qian et al, 2021 ). The dry season at the DJR occurs from February to July, and the wet season occurs from August to January of the following year.…”
Section: Discussionmentioning
confidence: 99%
“…An excess of NH 4 + and TN could readily lead to blooms of planktonic algae, resulting in a sharp decrease in the ratio between pro- and eukaryotes once these nutrients become beyond the threshold value of water safety ( Chen et al, 2018 ; Massey et al, 2020 ). Chl a is also closely related to algal blooms in water, and its drastic changes in concentration imply that the stability of the aquatic ecosystem has been damaged ( Massey et al, 2020 ; Zhang et al, 2020 ). The co-occurrence patterns of microbial taxa in aquatic ecosystems have revealed that environmental factors regulate the functional stability of keystone taxa by interfering with and changing their abundance ( Shade and Gilbert, 2015 ; Xue et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Water eutrophication caused by excess nitrogen and phosphorus lead to an explosion of algae and the consumption of dissolved oxygen (DO; Massey et al, 2020 ). Chemical oxygen demand (COD Mn ) and chlorophyll a (Chl a ) are decisive indicators of algal blooms and oxidizable organic pollutants ( Massey et al, 2020 ; Zhang et al, 2020 ), while Chl a and microbial abundance vary seasonally ( Li et al, 2017 ). The significant differences in total nitrogen (TN) and total phosphorus (TP) were found between different regions of a river in a previous study, distinctive effects of TN, DO and Chl a on pro- and eukaryotes were also observed in different seasons ( Sun et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…They can also be pathogenic and cause numerous diseases, which can seriously threaten global food security and human health (Head et al, 2014 ; Zhao et al, 2020 ). Despite the ecological significance of fungi, previous studies on microorganisms have mainly focused on the bacteria in lakes (Sadeghi et al, 2021 ; Shang et al, 2020 ; Shao et al, 2021 ), forests (Tian, He, et al, 2018 ; Zhu et al, 2020 ), oceans (Feng et al, 2009 ; Zhang, Liu, et al, 2021 ), and rivers (Qian‐Qian et al, 2021 ). Moreover, investigations on freshwater aquatic ecosystems, such as rivers and lakes, as main habitats of fungi have been limited (Khomich et al, 2017 , 2018 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%